BERJALAN DALAM HIKMAT ROH KUDUS BAGI PEMURIDAN KELUARGA KRISTEN - suhendra, Suhendra (UPPM Sekolah Tinggi Teologi Tabgha Batam, 2024)
The Holy Spirit, as the third coequal and consubstantial divine person of the Trinity, fulfills the promise to accompany churches as the Divine Person continuing the work of Jesus Christ. Through the wisdom poured out by the Holy Spirit, Christians are empowered to fulfill the Great Commission of Jesus Christ, including the process of Christian Family Discipleship. As emphasized by Paul the Apostle, every Christian possesses a genuine understanding of true wisdom, ensuring that the foundation of Christianity is not built on human wisdom but on divine wisdom. This article aims to underscore the significance of Holy Spirit wisdom in Christian Family Discipleship. The research methodology employed is Descriptive Qualitative (Sonny Eli Zaluchu 2020) with a literature review approach, drawing from sources such as the Bible, books, and relevant journals. The discussion encompasses the Holy Spirit's role in the world and the family, His strengthening of the weak, and His impartation of wisdom. Additionally, the article delves into the Biblical basis of the Holy Spirit's role in both the Old and New Testaments. The conclusion highlights the crucial importance of the wisdom bestowed by the Holy Spirit, as it not only reflects the highest wisdom of God but also greatly benefits Christian Family Discipleship.